No greater threat : America after September 11 and the rise of a national security state - Michaels, C. William (Algora Pub., 2002)
A pertinent analysis of the "USA Patriot Act," based on meticulous legal research and straight talk, points to America's ominous evolution into a national security state. "In this very important study, C.W. Michaels gives us a unique guide and commentary, based on meticulous research, to the ominous growth of the national security state. "His analysis of the 'USA PATRIOT Act' is immensely useful and a wake-up call for all Americans concerned with defending our civil liberties." Howard Zinn Author, A People's History of the United States "Congress had no time to read the USA PATRIOT Act before overwhelmingly passing it with great haste. A number of us (on the Left and Right) at the time stood up and pleaded the case for careful action, to little avail. Now, we all across the country must read and understand this statute - aided in significant part through Mr. Michaels' book - and learn the detail of other administrative actions after 9/11. Then we will be well-equipped to organize nationally and demand fixes to laws and practices that would be both constitutional and workable, rather than what we are seeing today."--Kit Gage, Director, First Amendment Foundation, Coordinator, National Coalition to Protect Political Freedom. An attorney and former law school academic explains why the USA PATRIOT Act ranks as one of the most significant pieces of legislation in many years, and examines the prospect that America (with the Congress and the Executive Branch in the lead) may be transforming itself into a national security culture. The book identifies and examines 12 common characteristics of a national security state, and discusses how those characteristics are being fulfilled today (in some instances, in an accelerated manner), and provides a meticulous description of each of the ten parts of the PATRIOT Act (so often discussed, so seldom explained). The Act grants broad powers to Federal investigators in surveillance, intelligence, prosecution, and inter-agency information sharing; and most of its provisions are permanent. C. William Michaels, Esq., is an attorney and writer living in the Baltimore area. Mr. Michaels has been involved in social issues and organizations for more than 30 years; he held a full-time position as Justice and Peace Coordinator with the Catholic Archdiocese of Baltimore (1982 to 1986). He has worked as a journalist and newspaper editor, and wrote, hosted, and organized a weekly half-hour radio program, New Earth Radio (1989 to 1991) and a weekly cable-access television program, WorldViews (1994 to 1996). He taught law at the University of Baltimore. A graduate of the University of Maryland School of Law, Mr. Michaels conducts an appellate law practice